Colour and Form Perception: Straddling the Boundary - Galina V. Paramei (Frontiers Research Topics, 2016)
Starting from psychophysics, over the last 50 years, most progress in unravelling the mechanisms of color vision has been made through the study of single cell responses, mainly in LGN and striate cortex. A similar development in the study of form perception may seem to be underway, centred on the study of temporal cortex. However, because of the combinatorial characteristics of form perception, we are also observing the opposite tendency: from single-cell activity to population coding, and from static receptive field structures to system dynamics and integration and, ultimately, a synthetic form of psychophysics of color and form perception. From single cells to system integration: it is this development the present Research Topic wishes to highlight and promote. How does this development affect our views on the various attributes of perception? In particular, we are interested in to what extent evolving knowledge in the field of color perception is relevant within a developing integrative framework of form perception. The goal of this Research Topic is to bring together experimental research encompassing both color and form perception. For this volume, we planned a broad scope of topics - on color in complex scenes, color and form, as well as dynamic aspects of form perception. We expect that the Research Topic will be attractive to the community of researchers whose work straddles the boundary between the two visual perception fields, as well as to the wider community interested in integrative/systems neuroscience.